The effect of oxidative stress on vitiligo patients - Mohammed Hasnawi Ali; Muthanna M. Awad (Indian Journal of Forensic Medicine & Toxicology, 2021)
The purpose of the study to shed light on one of the hypotheses keys in causing disease vitiligo is thestress hypothesis of oxidative, stable of vitiligo have been identified active stages or on the basis of thedevelopment or the emergence of new spots in the past three months and the absence of new or patchesdevelopment in the past six months, the in a row, this study included three groups, all of them were male.The first group included the active group, patients with vitiligo of the active type30 the second person, thedormant group, includes static type vitiligo patients 25One person, the third, the control group (apparentlyhealthy) included20People. We have examined the serum levels of Superoxide Dismutase enzyme, catalaseenzyme, and Malondi- aldehyde, our results revealed that the level of higher than Malondi- aldehyde at thelevel of probability (P <0.05) In the serum of the disease group compared to the control group, a significantincrease in the activity of superoxide dismutase was observed in the serum of the disease group at the level ofprobability(P <0.05)Compared to the control group, the catalase activity decreased at the probability level(P <0.05) In the pathological group compared with the control group, our study shows that stress Oxidativehas a role in the physiology pathogenesis of vitiligo active and static. An imbalance of antioxidants wasobserved in the blood of active Vitiligo patients.